Correlation between Weather Parameters at Different Phenophases and Growth and Yield Parameters of Groundnut (Arachis hypogaea L.) - Krishna Murthy, S K; Rao, A Yogeswara (Annals of Arid Zone, 2016)
Agricultural productivity is greatly influenced by uncontrollable forces of weather. A field experiment was conducted at the Agricultural Research Station. Anantapur, on red sandy loam soils, to study the crop-weather relationship in groundnut’ during two khariF seasons of 1989 and 1990. While the fluctuations in weather during vegetative phase had little influence on crop growth, they had significant effect on the reproductive phase. Rise in night temperature during reproductive phase favored the ultimate pod yield and its attributes. Among the phenophases, pod filling was found most sensitive and fluctuations in weather, including water use, during this phase, controlled most of the final yield. Solar radiation did not show any significant influence on ultimate yield, since radiations received were sufficient to meet the minimum needs of the crop.